STUDY OF CHEMICAL COMPOSITION OF CAPSICUM ANNUUM PLANT - Sapayev Bayramdurdi; Saitkulov Foziljon Ergashevich; Haydarov G‘ayrat Shoyimovich (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article presents for the first time ancient data on the fruits of red hot pepper. The chemical composition of the plant, micro-, macroelements and their biochemical effects on the human body have been thoroughly studied.